Using Family Style Dining to Increase Social Interactions in Young Children. (May 2017) - Locchetta, Brandy M.; Barton, Erin E.; Kaiser, Ann
During family style dining (FSD), caregivers are encouraged to sit with children at the table to support, promote, and facilitate conversations. FSD is considered a best practice in child care and is encouraged by many early childhood agencies. However, there is no current research documenting the effects of FSD on mealtime interactions in the preschool environment. The purpose of the current study was to examine the effects of FSD on the social interactions of preschool children during mealtime, and any subsequent changes in the rate of teacher directives and praise statements. Results demonstrated increases in the rates of initiations by target children when FSD was implemented; however, the increases across children were modest. Also, teachers' rates of directives were not impacted by the use of FSD; that is, teachers' rates of directives were the same, on average, when using and not using FSD.